2021
DOI: 10.1002/ctm2.366
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced cofilin 1 promotes hepatocellular carcinoma progression by regulating the PLD1/AKT pathway

Abstract: 1. Cofilin 1 is overexpressed in HCC, especially in PVTT tissues. 2. Cofilin 1 is up-regulated in hypoxia condition and promotes HCC progression. 3. CFL1 binds to PLD1 and maintains PLD1 protein stability. 4. HIF-1α regulates CFL1 transcription and activates CFL1-PLD1-AKT axis in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…In this study, the expression of vimentin was significantly decreased and that of E‐cadherin was increased in PC‐11 and PC‐40 cells, indicating that knockout of PLD1 could attenuate EMT progression in CASKI cells, and this phenomenon was observed in mouse tumour tissues in vivo. Previous studies demonstrated that inhibition of PLD1 could attenuate tumour EMT in hepatocellular carcinoma mice, 21 and PLD1 mediated EMT in hepatocellular carcinoma 24 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, the expression of vimentin was significantly decreased and that of E‐cadherin was increased in PC‐11 and PC‐40 cells, indicating that knockout of PLD1 could attenuate EMT progression in CASKI cells, and this phenomenon was observed in mouse tumour tissues in vivo. Previous studies demonstrated that inhibition of PLD1 could attenuate tumour EMT in hepatocellular carcinoma mice, 21 and PLD1 mediated EMT in hepatocellular carcinoma 24 …”
Section: Discussionmentioning
confidence: 95%
“…Previous studies demonstrated that inhibition of PLD1 could attenuate tumour EMT in hepatocellular carcinoma mice, 21 and PLD1 mediated EMT in hepatocellular carcinoma. 24 The RAS/RAF/MEK/ERK (MAPK) signalling pathway is pivotal in the cell signalling cascade that regulates cell survival, growth, migration and invasion. 25…”
Section: Discussionmentioning
confidence: 99%
“…According to many previous studies, CFL1 has promiscuous physiological effects, including cell motility, cell apoptosis and lipid metabolism (8). Currently, many researches showed the pivotal role of CFL1 in the development of tumor (9,10). CFL1 was higher in tumor than paired-normal tissue, including pancreatic cancer, vulvar squamous cell carcinoma, hepatocellular carcinoma, esophagus cancer, and prostate cancer (7,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has demonstrated that HCC is the most serious tumor of hypoxia [ 9 ]. Abundant evidence is showing that hypoxia can induce an increase in tumor malignancy, including tumor progression, invasion and metastasis, contributing to poor prognosis in HCC [ 10 , 11 ]. Nowadays immune checkpoint inhibitors (ICI) have become an effective immunotherapy and are popularly used in the treatment of HCC [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%